Ustilaginoidea virens modulates lysine 2‐hydroxyisobutyrylation in rice flowers during infection. Issue 10 (1st August 2021) - Chen, Xiaoyang; Xu, Qiutao; Duan, Yuhang; Liu, Hao; Chen, Xiaolin; Huang, Junbin; Luo, Chaoxi; Zhou, Dao‐Xiu; Zheng, Lu
Abstract: The post‐translational modification lysine 2‐hydroxyisobutyrylation (Khib ) plays an important role in gene transcription, metabolism, and enzymatic activity. Khib sites have been identified in rice ( Oryza sativa ). However, the Khib status of proteins in rice flowers during pathogen infection remains unclear. Here, we report a comprehensive identification of Khib ‐modified proteins in rice flowers, and the changes in these proteins during infection with the fungal pathogen Ustilaginoidea virens . By using a tandem mass tag‐based quantitative proteomics approach, we identified 2, 891 Khib sites on 964 proteins in rice flowers. Our data demonstrated that 2‐hydroxyisobutyrylated proteins are involved in diverse biological processes. Khib levels were substantially reduced upon infection with U. virens . Chromatin immunoprecipitation polymerase chain reaction (PCR) and reverse transcription quantitative PCR analyses revealed that histone Khib is involved in the expression of disease‐resistance genes. More importantly, most quantified sites on core histones H3 were downregulated upon U. virens infection. In addition, the histone deacetylases HDA705, HDA716, SRT1, and SRT2 are involved in the removal of Khib marks in rice. HDA705 was further confirmed to negatively regulate rice disease resistance to pathogens U. virens, Magnaporthe oryzae, and Xanthomonas oryzae pv. oryzae ( Xoo ). Our data suggest that U. virens could modulate Khib in rice flowers during infection. Abstract : A tandem mass tag‐based quantitative proteomics approach identified proteins modified by lysine 2‐hydroxyisobutyrylation in rice flowers and showed that the rice false smut fungus modulates this post‐translational protein modification in rice flowers during infection.